ANALISIS PENDAPATAN USAHATANI PADI SAWAH SELAMA PANDEMI COVID-19 DI DESA WATUNONJU KECAMATAN SIGI BIROMARU KABUPATEN SIGI - Putri Ananda; Nurmedika Nurmedika (Universitas Tadulako, 2022)
This study aims to determine the income of lowland rice farming during the Covid-19 pandemic in Watunonju Village. Determination of the location is done intentionally (purposive), the number of respondents as many as 35 people from the population of rice farmers as many as 160 people. Determination of respondents using the Slovin formula. Analysis of the data used is income analysis. The results of this study show that the average total farming costs incurred during the Covid-19 pandemic are Rp. 6,562,208.06/1.1Ha/MT or Rp. 5,900,463.69/1.1Ha/MT. The average income obtained by farmers is Rp.15,176,571.42/1.1Ha/MT or Rp. 13,796,883.12/1.1Ha/MT of the average production of 1,686.28/1.1Ha/MT multiplied by the average selling price of rice at the farmer level of Rp. 9,000/Kg so that the average income of paddy rice respondent farmers in Watunonju Village during the Covid-19 Pandemic in one planting season is Rp. 8,614,363.37/1.1Ha/MT or Rp. 7,831,239.43/1.0/Ha/MT.